1983
DOI: 10.1136/sti.59.5.298
|View full text |Cite
|
Sign up to set email alerts
|

Cefaclor and cefamandole as alternatives to spectinomycin in the treatment of men with uncomplicated gonorrhoea.

Abstract: Cefaclor at a dose of 3 g given orally with 1 g probenecid appears to be an effective alternative to spectinomycin 2 g in the treatment of gonorrhoea in areas where strains of penicillinase producing Neisseria gonorrhoeae (PPNG) are prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A single report of intramuscular cefamandole Ig with oral probenecid Ig producing a failure rate of 29% suggests that this regimen is ineffective for treating N. gonorrhoeae (Panikabutra et al 1983). Alternatively, single intramuscular doses of cefonicid Ig in combination with Ig of probenecid by mouth produced a failure rate of only 2% (Sanchez et al 1984).…”
Section: Gonorrhoeamentioning
confidence: 97%
See 1 more Smart Citation
“…A single report of intramuscular cefamandole Ig with oral probenecid Ig producing a failure rate of 29% suggests that this regimen is ineffective for treating N. gonorrhoeae (Panikabutra et al 1983). Alternatively, single intramuscular doses of cefonicid Ig in combination with Ig of probenecid by mouth produced a failure rate of only 2% (Sanchez et al 1984).…”
Section: Gonorrhoeamentioning
confidence: 97%
“…Single oral doses of cefaclor 3g in combination with probenecid Ig have failure rates of 4.2% (Panikabutra et al 1983) and 7% (Tupasi et al 1982), which are less than the failure rate with an equivalent cefaclor dose administered alone (10.4%) [Panikabutra et al 1983]. Multiple day (3) regimens of cefaclor 2, 3 or 4g as a single daily dose in combination with Ig of probenecid produced failure rates of 9, 0 and 0%, respectively (Spagna et al 1979).…”
Section: Gonorrhoeamentioning
confidence: 98%
“…9 Panikabutra et al published a cure rate of 90% when cefaclor was administered as a 3 g single dose alone in Bangkok, Thailand, and of 96% when 3 g cefaclor and 1 g probenecid were administered jointly, although the difference between the two groups was not statistically significant. 2 Tupasi et al reported a 93% cure rate in 61 female patients with uncomplicated gonococcal infection who were given 3 g single dose with probenecid in Manila, Philippines.3 Finally, Spagna et al reported a cure rate of 98% in a study undertaken in Columbus, Ohio, but with a multiple dose treatment regimen. 4 Cefaclor and cefixime share the advantages of single oral administration, absence of toxicity in pregnancy, and lack of serious side effects.…”
Section: Discussionmentioning
confidence: 99%